Mini-implant selection protocol applied to MARPE - Lincoln Issamu Nojima; Matilde da Cunha Gonçalves Nojima; Amanda Carneiro da Cunha; Natan Oliveira Guss; Eduardo Franzotti Sant'Anna
Abstract Introduction: Rapid maxillary expansion (RME) is the therapy of choice to correct skeletal transverse dimension in children and adolescents, associating orthopedic and dental effects. In an attempt to prevent the undesirable dentoalveolar effects and optimize the potential of skeletal expansion in individuals in advanced stages of skeletal maturation, the miniscrew-assisted rapid palatal expander (MARPE) was proposed by Lee et al. in 2010. Objective: This paper presents a systematized protocol for selection of miniscrews indicated for MARPE, by the evaluation of cone-beam computed tomographies (CBCT). Variables related with the bone and soft tissue thicknesses at the palatal regions of interest, as well as in relation to the fixation rings of miniscrews of the palatal expander are analyzed and discussed to provide better performance in the clinical practice.